EFEK GETARAN PADA PENGELASAN ALUMINUM 5083 H112 MENGGUNAKAN PROSES LAS GAS METAL ARC WELDING (GMAW) TERHADAP POROSITAS - Imam Khoirul Rohmat; Winarto Winarto (P3M Politeknik Negeri Indramayu, 2018)
5083 series aluminum magnesium is widely used for marine industrial. It is caused aluminum has high specific strength and good corrosion resistance. However, at process of welding many of porosity occured in the aluminum and it decrease the mechanical properties especially in HAZ (Heat Affected Zone). At casting process of aluminum, porosity could reduce by giving vibration. So, this method is tried to be applicated for welding of aluminum due to welding is a miniature of casting. Tensile test, hardness test, metallography test, and image analysis are technique to characterize the effect. As a result, vibration is not really affected the amount of porosity that occurred. But for hardness it is influenced especially for ER 4043 filler where the vibrated specimens have a higher hardness. The higher average result of tensile test for ER 5356 filler obtained at unvibrated specimens with the value is 231 MPa and for ER 4043 filler the higher average result obtained at vibrated specimen, the value is 226 MPa.